Four Restoration marriage plays - Otway, Thomas 1652-1685; Lee, Nathaniel 1653-1692 (Oxford drama library, 1995)
Marriage and its discontents lie at the heart of Restoration comedy. In all four of the plays gathered together here for the first time, a married woman confronts her would-be seducer. Each dramatist, however, totally reinterprets that situation. Thomas Otway's The Soldier's Fortune converts adultery into political revenge. Nathaniel Lee's The Princess of Cleves offers a potent and perplexing portrait of a libertine in action at the sixteenth-century French court. John Dryden's Amphitryon, set in ancient Thebes, retells the story in which Jupiter lures virtuous Alcmena into cuckolding her husband by a stratagem which throws into doubt the nature of human identity. Thomas Southerne's The Wives' Excuse reinvents, for the new circumstances of the 1690s, the familiar Restoration plot of a wife spurred towards infidelity by her partner's failings